Effect of smartphone applications before deep learning: promoting physical activity enjoyment and physical fitness among children with disabilities - Dimyati, Akhmad; Dermawan, Dikdik Fauzi; Mahardhika, Dhika Bayu; Gani, Ruslan Abdul; Setiawan, Edi (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2026)
Background: The use of smartphone applications (SA) before deep learning (DL) is currently showing an increase in popularity in the context of physical education (PE) teaching, but the effects smartphone applications within deep learning (SADL) on physical activity enjoyment (PAE) and physical fitness (PF) are still unclear. Objectives: Our current study aims to analyse the effects of SADL on PAE and PF among students with disabilities. Methods: This study adopted an experimental design with a 10-week pretest-posttest design. We involved 40 participants with disabilities from two schools in Karawang (Indonesia). They were allocated to the SADL (n = 20) and control group (CG, n = 20). PAE and PF assessments were conducted twice, at the pretest and posttest stages. Results: Our main findings prove that there was no difference in PAE and PF scores between the SADL and CG at the pretest stage, but we found different results at the posttest stage, which showed that there was a difference in PAE and PF scores between the SADL and CG. Conclusion: The findings suggest that integrating smartphone applications within a deep learning framework may enhance physical activity enjoyment and selected components of physical fitness among students with disabilities.